DELAYED-ONSET STREPTOCOCCUS INTERMEDIUS ENDOPHTHALMITIS FOLLOWING ANTI–VASCULAR ENDOTHELIAL GROWTH FACTOR INTRAVITREAL INJECTION. Issue Volume 16:Issues 6(2022) (November 2022) - Mercer, Gareth D.; Politis, Michael; Campagnoli, Thalmon R.; Galic, Ivan J.; Chen, John C.
Abstract : We show a case of endophthalmitis presenting 7 weeks after intravitreal aflibercept injection. An unusual species of viridans streptococci, S. intermedius, was isolated. The case highlights the need to consider infection even in cases of very delayed-onset postinjection inflammation, and the potential wide variability in severity of Streptococcus viridans endophthalmitis. Abstract : Purpose: Endophthalmitis following intravitreal anti–vascular endothelial growth factor injections is frequently caused by Streptococcus viridans organisms and tends to be aggressive. Herein, we present a case of postinjection Streptococcus viridans endophthalmitis presenting in an atypically delayed fashion with good visual outcome. Methods: Single clinical case report. Results: A 91-year-old woman treated with aflibercept for exudative age-related macular degeneration of the left eye presented to the emergency department with mild pain and visual acuity decline to counting fingers, pigmented anterior chamber cells and vitreous haze 7 weeks after her most recent intravitreal injection. She had no symptoms of systemic infection. The presumptive diagnosis initially was vitreous hemorrhage. Over 10 days of observation, she developed worsening pain and vitritis suggestive of endophthalmitis, leading us to perform vitrectomy with intravitreal vancomycin and ceftazidime. Vitreous biopsy was culture positive for Streptococcus intermedius, a type of viridans streptococcus typically associated with head and neck abscesses. The infection resolved and the patient's visual acuity returned to her baseline of 20/100, with no recurrence of infection after 4 months of follow-up. Conclussion: The virulence of viridans streptococci capable of producing postinjection endophthalmitis may vary widely. Infection ought to be suspected even in cases of delayed-onset intraocular inflammation.